Website Penjualan Pada Gerai Rabbani Pontianak Menggunakan Framework Laravel - Maulidania, Resvi; David, Davi; Yuliani, I Dewa Ayu Eka; Kosasi, Sandy; Syarifudin, Gusti (Jurnal Informatika dan Komputer, 2024)
Rabbani Store is a business that operates in the field of selling hijabs, clothing and other accessories which currently still uses a conventional or simple system, where the transaction and shopping process still requires consumers to come directly to the shop, so they wait to find out whether the goods are still in stock. or not. To overcome this problem, a sales website is needed at Rabbani Stores so that the sales system at Rabbani Stores can be further developed because it is online or digital based. Consumers no longer need to come to the store and wait a long time to shop, and consumers can make transactions directly from the sales website. In designing this sales website using the Laravel Framework by applying the MVC concept. The design method used is the Extreme Programming method. The research method used is Design Science Research (DSR). The results of this research produced a sales website at Gerai Rabbani using the Laravel Framework so that it could help sales at Gerai Rabbani. The conclusion of the designed website is that it can help the shop owner of Gerai Rabbani to market the products being sold. The suggestion is that the website used needs to be further developed in the interface so that it is easier and more attractive for users to use.